Metallic Pollutant Removal in Leachates Extracted from Sediment by Geotextiles Based on Crosslinked Bio-Sourced Polymers - Degoutin, Stéphanie; Saffre, Camille; Ruffin, Delphine; Bacquet, Maryse; Martel, Bernard (Revue des sciences de l’eau / Journal of Water Science, 2015)
The aim of this study was to prepare ion exchange textiles (IET) by grafting carboxylic functions onto the surface of polyethylene terephthalate (PET) nonwoven fabrics in order to capture metals in leachates extracted from dredged sediment samples, taken from Dunkerque seaport. A pad/dry/cure coating process, based on the in situ polymerization of a mixture consisting of maltodextrin and a polycarboxylic acid on the textile structure, was applied. We used either citric acid (CTR) or 1,2,3,4-butanetetracarboxylic acid (BTCA) as polycarboxylic acids. The amount of ion exchange functions on the geotextiles was first measured and we evaluated their adsorption capacities towards metal cations. To reach that purpose, a first test was carried out on solutions prepared with lead (Pb) in the absence or presence of NaCl, to mimic seawater saline conditions. The presence of NaCl led to a moderate reduction of 25% in lead removal by the IET. The second test was carried out on a sediment leachate. This leachate being weakly contaminated, we artificially doped it with cadmium, copper, lead and zinc in order to evaluate the potential utility of the geotextile treatment. The functionalized textiles adsorbed more than 60% of the lead and zinc. A complete removal of copper was reached for CTR-based IET and the textiles showed less efficiency towards cadmium in the considered mixture.